中醫現代化研究: 證實與證偽: Modernizing Traditional Chinese Medicine: Confirmation and Falsification - QIU, Hongzhong (International Journal of Chinese & Comparative Philosophy of Medicine, 1998)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文回顧總結了近幾年中國本土中醫現代化研究的基本狀況和學術焦點，認為邏輯實證只是中醫現代化研究的一個主流方面，中醫還需要證偽。去偽存真是不可分割的兩面。目前許多爭議與分歧源出民族文化的自尊和認知偏見，確立一種公正的文化比較觀和認知方法對於糾正中醫現代研究中的那些“唯科學主義”和民族偏見都是至關重要的。中醫現代化研究的重新定位是走向後現代的思維。 Most contemporary research concerning modernizing traditional Chinese medicine is aimed at confirming the effectiveness of certain traditional doctrines, methods, and treatments through scientific experiments designed in terms of modern scientific theories and approaches. This paper argues that such research should also consider the issue of falsification. Not everything in traditional Chinese medicine can be confirmed. We need a complete mechanism through which to reject the false and maintain the true. By investigating several major academic journals in the field published in mainland China, we find that there have been several different types of research concerning modernizing traditional Chinese medicine. First, the modern Western pattern of clinical trial has been used to test the effectiveness of traditional Chinese drugs. Second, modern Western medical ways have been employed in administering traditional Chinese drugs to patients. Third, modern scientific experiments have been designed to analyze the chemical components of traditional Chinese drugs and disclose their functional mechanisms at the micro-level of the body. Fourth, efforts have been made to explain and reformulate traditional Chinese medical theories and clinical experience in terms of modern scientific and medical theories. Finally, modern medical methods and technologies have been chosen to test particular traditional Chinese clinical doctrines and principles. All of this research has been very helpful for us to understand traditional Chinese medicine in terms of modern science and technology. However, some scholars are worried that such research has abandoned the identity of traditional Chinese medicine as a peculiar medical system. They doubt that the diagnostic and therapeutic doctrines and approaches of traditional Chinese medicine can be subject to the investigation and test of modern scientific theories and methods without destroying their very characteristics. However, these scholars fail to see a crucial role played by the method of experimental research in selecting scientific hypotheses and theories. Traditional Chinese medicine, as a medical system, ought to be open to the test of experimental research to confirm its useful parts and falsify its false components. Only through this process of differentiation can traditional Chinese medicine become a real scientific system in the modern sense. DOWNLOAD HISTORY | This article has been downloaded 25 times in Digital Commons before migrating into this platform.